Numerical Investigation of Fluid-Structure Interaction with Mixed Convection in an Open Cavity of Flexible Wall: Effect of Geometrical Parameters - A. Sabbar, Walaa; A. Ismael, Muneer; Almudhaffar, Mujtaba (International Journal of Engineering and Technology, 2018)
The object of this paper is the mixed convection and fluid flow in a cavity consisting of a flexible wall linked to a horizontal channel. A heat source segment fixed on the bottom wall while all other solid walls are thermally insulated heats up the cavity. Fluid structure interaction (FSI)is taken into account and the arbitrary Lagrangianâ€“Eulerian (ALE) technique with FEM are adopted together to solve the discretized formulations. Impacts of various parameters on the heat exchange were investigated, these are: the channel height to cavity height ratio, represented by (H/D) = 0.5â€“1.1;heat source length, LH= 0.5 â€“ 1.5;heat source location, and Ri = 0.1- 100. The results show that (H/D) has marginal impact on the Nusselt number, where only 5% enhancement is associated at H/D = 0.7 for Ri = 100. The lower the length of the heat source is the maximal the Nusselt number. A maximum enhancement in the Nusselt number of 156% is obtained when LH is decreased from 1.5 to 0.5.Â Â